Mechanical and physical properties of oil palm trunk core particleboard bonded with different UF resins - Lee, Seng Hua; H'ng, Paik San; Lum, Wei Chen; Ashaari, Zaidon; Bakar, Edi Suhaimi; M. Y., Nurliyana; Chai, Ee Wen; Chin, Kit Ling (Malaysian Palm Oil Board, 2014)
Rapid price increases and reduction in the supply of rubberwood has forced the particleboard manufacturers to look for new alternative raw materials. The production of particleboard from other wood species will be a good solution to the problem of depleting wood supplies. The objective of this study was to evaluate the properties of particleboard made from rubberwood and oil palm trunk pressed at different temperatures and times compared to particleboards made from single species. Two types of UF resins (E1 resin and SE0 resin) were applied in this study. The effect of surface-to-core ratio was also examined in this study. The modulus of rupture, internal bond strength and thickness swelling of the boards were evaluated based on the Japanese Industrial Standard for particleboard (JIS A 5908:2003). After evaluation, the panels produced are a potential substitute to the panels made from pure rubberwood.